Unusual presentation of glioblastoma in the brainstem: a case report of a diffuse pontine glioblastoma multiforme and surgical management - Edelbach, Brandon; Gospodarev, Vadim; Lopez-Gonzalez, Miguel; Deisch, Jeremy; Kaur, Maninder (Frontiers in Oncology, 2024)
Diffuse pontine glioblastoma multiforme is a rare subtype of glioblastoma associated with a poor prognosis. In this case report, we present a unique case of diffuse primary pontine glioblastoma multiforme in a patient without any supratentorial lesions. We review the symptoms, treatment options, and case management of patients with infratentorial glioblastoma multiforme and compare these with our patient. Our patient presented with symptoms including progressive diplopia, gait disturbance, and lower extremity weakness. Magnetic resonance imaging revealed a diffuse lesion involving the pons and biopsy revealed only mildly-atypical glial infiltrates. Consequentially, diagnosis was driven by genetic analysis. Due to the location of the tumor, surgery was not considered a viable option. Instead, the patient received radiation therapy along with concomitant and adjuvant temozolomide chemotherapy which has resulted in improvement of symptoms. This case highlights the challenges of managing diffuse primary pontine glioblastoma multiforme and the need for more effective treatment options for this rare subtype of glioblastoma. Despite aggressive treatment, the prognosis for patients with infratentorial glioblastoma multiforme remains poor, with a median survival time of less than a year. Further research is needed to improve our understanding of the biology and optimal management of this disease.